Observational study of the effects of silver-based dressing materials in 50 cases of diabetic foot ulcers - Patel, Daxesh; Maisuria, Rushabh; Manza, Jawansing; Chaudhari, Devendra; Dave, Divyang (International Surgery Journal, 2019)
Background: Diabetic foot remains the most common chronic medical problem being the most common cause of the hospital visit and/or admission, amongst the diabetic patients. Topical antimicrobial dressings, including those that contain silver are used to prevent or manage infection in a wide range of wounds. Methods: This is the prospective, observational study which included 50 cases of diabetic foot ulcer patients and effects of silver-based dressing materials will be evaluated. Results: After application of silver based dressing materials for two weeks, wound was evaluated on the basis of discharge from the wound, healing rate, appearance of the granulation tissue and culture and sensitivity report which showed that out of 50 cases studied, 3 cases (6%) had purulent discharge from the wound, absent granulation tissue, culture report showed presence of micro-organism and thus poor healing rate while other 47 cases (94%) had minimal/serous discharge, presence of healthy granulation tissue, no organism on culture report and thus good healing rate. Conclusions: Silver based dressing materials are effective in terms of promoting wound healing and more patient compliance.